2014
DOI: 10.1155/2014/589846
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Bu‐Shen‐Huo‐Xue Formula against 5/6 Nephrectomy‐Induced Chronic Renal Failure in Rats

Abstract: Chronic renal failure (CRF) is a serious disease related to increasing incidence and prevalence as well as decline in quality of life. Bu-Shen-Huo-Xue formula (BSHX), one of traditional herbal formulations, has been clinically employed to treat CRF for decades, but the mechanisms involved have not been investigated. In the present study, we investigated the effects of BSHX on some closely related parameters in 5/6 nephrectomy CRF rats. Rats with CRF were divided into five groups, namely, one control group, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Although a lot of researches have been made to better understand the pathogenesis of CKD, there are no good drugs for treatment of these kinds of diseases. In China, traditional Chinese medicine (TCM) is used for the treatment of CKD and its complications, [13] which can be developed into the new therapeutic agents. ShenKang injection (SKI), a Chinese Material Medica-standardized product extracted from Rhubarb, Astragalus, Radix Salviae miltiorrhizae and Carthami Flos, is formulated base on TCM theory and widely applied in clinical treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of researches have been made to better understand the pathogenesis of CKD, there are no good drugs for treatment of these kinds of diseases. In China, traditional Chinese medicine (TCM) is used for the treatment of CKD and its complications, [13] which can be developed into the new therapeutic agents. ShenKang injection (SKI), a Chinese Material Medica-standardized product extracted from Rhubarb, Astragalus, Radix Salviae miltiorrhizae and Carthami Flos, is formulated base on TCM theory and widely applied in clinical treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that traditional Chinese medicine have beneficial effect on treating CRF (19,20). Li et al (21) reported that icariin-treated human umbilical cord mesenchymal stem cells could improve kidney function via reduced inflammatory responses and oxidative damage in CRF rats.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study indicated that APS, a component of traditional Chinese medicine, may protect muscle cells in vivo and in vitro from atrophy associated with CRF (cachexia). Other studies have reported that traditional Chinese medicine have beneficial effect on treating CRF ( 19 , 20 ). Li et al ( 21 ) reported that icariin-treated human umbilical cord mesenchymal stem cells could improve kidney function via reduced inflammatory responses and oxidative damage in CRF rats.…”
Section: Discussionmentioning
confidence: 99%
“…The 5/6 nephrectomized rat model, involving unilateral nephrectomy and either partial infarction or amputation of the poles of the remaining kidney, represents the primary option for the investigation of CKD ( 4 , 33 , 34 ). Lu et al reported kidney dysfunction, with significantly elevated BUN and SCr levels and histopathological changes (glomerular sclerosis and interstitial fibrosis) in a 5/6 nephrectomized rat model ( 34 ). The 5/6 nephrectomized model of CKD has demonstrable clinical relevance ( 5 , 35 , 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each rat was anesthetized with chloral hydrate solution (33 mg/100 g) via intraperitoneal injection. A total of 18 rats was subjected to 5/6 nephrectomy (5/6 Nx) in which, the upper and lower poles of the left kidney and the entire right kidney were removed, as previousy described ( 5 , 34 , 35 ). A sham operation was performed on 6 additional rats as a non-Nx control (sham-operated) group.…”
Section: Methodsmentioning
confidence: 99%